NS5806 Induces Electromechanically Discordant Alternans and Arrhythmogenic Voltage-Calcium Dynamics in the Isolated Intact Rabbit Heart - Wang, Sufen; Rodríguez-Mañero, Moisés; Ibarra-Cortez, Sergio H.; Kreidieh, Bahij; Valderrábano, Laura; Hemam, Majd; Tavares, Liliana; Blanco, Elvin; Valderrábano, Miguel (Frontiers in Physiology, 2019)
Background: NS5806, activates the transient outward potassium current, Ito, and has been claimed to reproduce Brugada Syndrome (BrS) in ventricular wedge preparations. Ito modulates excitation-contraction coupling, which is critical in alternans dynamics. We explored NS5806-arrhythmogenic effects in the intact whole heart and its impact on alternans. Methods: Langendorff-perfused rabbit hearts (n=20) underwent optical AP and Ca mapping during pacing at decremental cycle lengths (CL). Spontaneous arrhythmias, and pacing-induced alternans were characterized at baseline (BL), after perfusing with NS5806, before and after adding verapamil (VP), and SEA0400 (SEA, n = 5 each), to modulate Ca-current and Na-Ca exchange, the main AP-Ca coupling mechanisms. Results: NS5806 induced BrS-like ECG features in 6/20 hearts. NS5806 prolonged steady-state (3Hz) APD by 16.8% and Ca decay constant by 34%, and decreased conduction velocity (CV) by 52.6%. After NS5806, spontaneous ventricular ectopy (VE) and AP/Ca alternans occurred. Pacing-induced alternans during NS5806 infusion occurred at longer CL and was AP/Ca discordant from its onset. Spatially discordant alternans after NS5806 had non-propagation-driven nodal line distribution. No spontaneous phase-2 reentry occurred. Under NS5806+VP, alternans became AP/Ca concordant and only induced in 2/5; NS5806+SEA did not affect alternans but suppressed spontaneous ectopy. Conclusions: NS5806 disrupts AP-Ca coupling and leads to Ca-driven, AP/Ca-discordant alternans and VE. Despite BrS-like ECG features, no spontaneous sustained arrhythmias or phase-2 reentry occurred. NS5806 does not fully reproduce BrS in the intact rabbit heart.